The Impact of Broadcasters on Consumer’s Intention to Follow Livestream Brand Community - Wang, Wei; Huang, Minxue; Zheng, Shiyong; Lin, Liangtong; Wang, Lei (Frontiers in Psychology, 2022)
As the essence of livestream e-commerce is social commerce, building a livestream brand community and attracting brand followers are the key aspects to achieving sustained revenue. For many companies, inviting celebrities has become a shortcut to attract new followers. Considering the unsustainability and high cost of the celebrity host mode, some companies switched to using their own branded broadcasters to attract followers. However, as branded broadcasters lack a fan base, choosing the suitable broadcaster type has become a challenge in livestream e-commerce. The motivation of consumers to follow brand livestream accounts is mainly to obtain potential value by embedding them in social networks. Therefore, based on motive theory, this research explores how different broadcaster types affect consumer’s intention to follow a livestream brand community. Results from the analysis of secondary data from livestream platforms and two laboratory experiments reveal that (1) celebrities contribute more to consumer’s intention to follow than branded broadcasters, and utilitarian (vs. hedonic) products can strengthen the effect of branded (vs. celebrity) broadcasters on attracting potential followers. (2) Moreover, branded (vs. celebrity) broadcasters can promote consumer’s intention to follow a livestream brand community by satisfying consumer’s need for informational (vs. emotional) value during utilitarian (vs. hedonic) product evaluation. This research analyzes the differential effects of different types of broadcasters on livestream brand community building. The findings can deepen the understanding of the consumer’s behavior of following brand livestream communities and provide companies with suggestions on broadcaster selection in livestream e-commerce.